Integrated Analysis of Microtremor Horizontal to Vertical Spectral Ratio, Surface Waves Dispersion Curve, and Seismic Refraction Tomography to Estimate Weathered Layer Thickness and Seismic Vulnerability: Case Study Kalirejo Village, Kokap Sub-District, Kulon Progo Regency - Anna Wahyu; Ade Filla Intan; Arddhiles Adhitama; Febrian Nur Fadhli; Ferda Elita Putri; Gunarta Sutantio; Henest Paskah; Intan Permata Sari; Kirana Ndaru Pertiwi; Luthfan Kin Gumandar; Milya Dwi Lestari; Naufal Abdila; Neneng Alif Karlina; Nita Utami; Patria Ufaira Aprina; Reymon Arga Medika (Department of Physics Universitas Gadjah Mada, 2020)
Subduction of Indo-Australia plate to Eurasia plate and locally active fault nearby Kulon Progo play as major source for earthquake events. After effect due to earthquake has different level of damage which depend on the magnitude and site characteristics. The horizontal-to-vertical spectral ratio (HVSR) passive seismic method is being used drastically to help in mapping the level of site vulnerability to earthquake event. HVSR analysis results help us acquire some physical values including weathered layer thickness where Vs 30 reference came from surface waves dispersion curve analysis of the MASW method as it is used as a parameter in calculating thickness value. Seismic refraction tomography is used to create subsurface model thus we may see the extent of underlying layer and its implication to earthquake event.Data measurements distribution are scattered in Kalirejo Village with the total of 63 passive seismic data, 33 MASW data, and 7 lines of seismic refraction acquisition. Some data show inadequate quality to be taken into further processing step, so data sorting activity should be carefully done. As a result, 21 of 63 passive seismic data are considered adequate to represent site physical values. Dominant frequency values ranging from 2 to 20 Hz, amplification factor varies between 1.5-12.5, and seismic vulnerability indices varies between 0.3-20. Surface waves dispersion curve inversion results are Vs 30 values ranging from 350 m/s to 980 m/s and seismic refraction tomography model shows Vp model with velocity values ranging from 0.2 to 3.2 km/s.